2021
DOI: 10.2139/ssrn.3896131
|View full text |Cite
|
Sign up to set email alerts
|

Catch Me (If You Can): Assessing the Risk of SARS-CoV-2 Transmission Via Euro Cash

Abstract: Disclaimer: This paper should not be reported as representing the views of the European Central Bank (ECB). The views expressed are those of the authors and do not necessarily reflect those of the ECB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The European Central Bank responded to this public concern by conducting a study on the survivability of COVID-19 on their banknotes. The study concludes that "as for many other similar viruses, SARS-CoV-2 survives on banknotes and coins for 30 min to a maximum of several days (significantly shorter than on door handles, for instance), but only in limited quantities" [29] (p. 15). The unprecedented public concern has led central banks in countries such as China, South Korea, Hungary, and Kuwait to implement measures to sterilize or quarantine banknotes to ensure that cash leaving their currency centers does not carry viruses [26].…”
Section: Fintech Adoption and Fear Of Covid-19 From A Pmt Perspectivementioning
confidence: 93%
See 1 more Smart Citation
“…The European Central Bank responded to this public concern by conducting a study on the survivability of COVID-19 on their banknotes. The study concludes that "as for many other similar viruses, SARS-CoV-2 survives on banknotes and coins for 30 min to a maximum of several days (significantly shorter than on door handles, for instance), but only in limited quantities" [29] (p. 15). The unprecedented public concern has led central banks in countries such as China, South Korea, Hungary, and Kuwait to implement measures to sterilize or quarantine banknotes to ensure that cash leaving their currency centers does not carry viruses [26].…”
Section: Fintech Adoption and Fear Of Covid-19 From A Pmt Perspectivementioning
confidence: 93%
“…Without disqualifying the role of rules and regulation in shaping behavior, there are sufficient reasons to argue that users' behavioral shifts have also driven FinTech adoption during the pandemic [28]. COVID-19 is a highly contagious acute respiratory virus (SARS-CoV-2) transmittable through physical contact with infected humans or objects, including banknotes and coins [26,29]. Studies by [23][24][25] have shown that the fear of becoming infected has changed consumer spending and purchasing behavior toward online platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that the likelihood that of getting COVID-19 via payment instruments is low. For example, Tamele et al (2021) report a very low risk of getting the virus via the use of cash. Schijven et al (2021) also find a very low risk.…”
Section: Related Literaturementioning
confidence: 99%
“…As a result, numerous concerns have been raised, that banknotes and coins serve as vectors for the transmission of disease-causing microorganisms. During the recent COVID-19 pandemic, it was suspected that contaminated banknotes and coins contributed to the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), resulting in a sharp decline in the use of cash ( Tamele et al., 2021 ).…”
Section: Before You Beginmentioning
confidence: 99%